Life-Cycle Impact Assessment of Fossil Power Plants with and without Co2 Capture Evaluating the Possibility of Co2 Utilization - Tarannum, Nafisa; Brishti, Banhee Shikha Roy; Dima, Sadia Siddika; Kirtania, Kawnish (Chemical Engineering Research Bulletin, 2021)
The CO2 emission is more than 36 billion tons per year in global scale. As carbon dioxide emission raises global temperature by trapping solar energy in the atmosphere, research is ongoing to facilitate the capture of CO2 with high efficiency. While CO2 footprint of Bangladesh is relatively low, with upcoming coal-based power plants (>17000 MW) in the next decade, fossil CO2 emission will increase significantly. To understand the underlying benefit of CO2 capture process, cradle-to-gate life cycle impact assessment (LCIA) of the power plants using fossil sources (e.g. natural gas, coal) can provide an in-depth insight. This paper aims to conduct life cycle impact assessment on natural gas and coal (sub critical and supercritical) fired power plants with and without CO2 capture facility for comparison of overall impact on the environment. An open source software titled OpenLCA was used to carry out LCIA and study different impact parameters (i.e. green-house gas emission, toxicity and ozone layer depletion). It was found that the CO2 emission from super-critical pulverized coal (SCPC) and sub-critical pulverized coal (Sub-PC) fired power plants could be brought down by more than 80% using CO2 capture facility. Along with capture, it is equally important to ensure proper sinks for this captured CO2. As Bangladesh has no dedicated geological reservoir for CO2 storage, potential sink for captured CO2 could be immediate utilization after capture. This paper also presents preliminary results on utilizing CO2 through mineralization during preparation of alternative admixture and construction materials. Due to the ever-growing real-estate sector of Bangladesh, there is great potential in capturing and utilizing CO2 through construction activities. Chemical Engineering Research Bulletin 21(2020) 88-93